2010
DOI: 10.1590/s0103-84782010001200002
|View full text |Cite
|
Sign up to set email alerts
|

Número de repetições para avaliação de caracteres de produção, fenologia e morfologia de cultivares de feijão

Abstract: RESUMO O objetivo deste trabalho foi determinar o número de medições (repetições), necessário à predição do desempenho de cultivares de feijão (Phaseolus vulgaris L.). Quatorze cultivares foram avaliadas em nove experimentos conduzidos ABSTRACT The aim of this research was to determine how many evaluations (replications) were necessary to predict the performance of common bean cultivars. Fourteen common beans cultivars (Phaseolus vulgaris L.) were evaluated in nine experiments conducted at Santa Maria, in Rio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
5
0
3
Order By: Relevance
“…Além da produtividade de grãos, o dimensionamento do número de repetições para avaliar outros caracteres de feijão (Cargnelutti & Ribeiro, 2010), de soja (Cargnelutti & Gonçalves, 2011) e de milho (Cargnelutti & Guadagnin, 2011) tem sido realizado a partir do coeficiente de repetibilidade. De maneira geral, nesses estudos foi evidenciado que, para a mesma precisão, há variabilidade do número de repetições entre caracteres.…”
Section: Introductionunclassified
“…Além da produtividade de grãos, o dimensionamento do número de repetições para avaliar outros caracteres de feijão (Cargnelutti & Ribeiro, 2010), de soja (Cargnelutti & Gonçalves, 2011) e de milho (Cargnelutti & Guadagnin, 2011) tem sido realizado a partir do coeficiente de repetibilidade. De maneira geral, nesses estudos foi evidenciado que, para a mesma precisão, há variabilidade do número de repetições entre caracteres.…”
Section: Introductionunclassified
“…The variability of r between traits and trials is particularly important in this study by representing different real situations that enable inferences regarding J, with overall applications. The variability of r and, subsequently, estimation of J between traits and trials were also observed in common bean Cargnelutti Filho and Ribeiro, 2010), soybean Cargnelutti Filho and Gonçalves, 2011), maize Cargnelutti Filho and Guadagnin, 2011), and irrigated rice (Cargnelutti Filho et al, 2012).…”
Section: Resultsmentioning
confidence: 78%
“…Therefore, we can infer that there was variability in the experimental accuracy between traits and tests but that, in general, these traits were evaluated under satisfactory experimental conditions. The variability of experimental accuracy, based on SA between traits and tests, has been verified in studies with common bean (Cargnelutti Filho and Ribeiro, 2010), soybean (Cargnelutti Filho and Gonçalves, 2011), maize (Cargnelutti Filho and Guadagnin, 2011), and irrigated rice (Cargnelutti Filho et al, 2012) genotypes.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations